2021
DOI: 10.1182/blood.2020007731
|View full text |Cite
|
Sign up to set email alerts
|

Osteocytes regulate neutrophil development through IL-19: a potent cytokine for neutropenia treatment

Abstract: Osteocytes are the most abundant (90-95%) cells in bone and have emerged as an important regulator of hematopoiesis, but their role in neutrophil development and the underlying mechanisms remain unclear. Interleukin (IL)-19 produced predominantly by osteocytes stimulated granulopoiesis and neutrophil formation, which stimulated IL-19 receptor (IL-20Rb)/Stat3 signaling in neutrophil progenitors to promote their expansion and neutrophil formation. Mice with constitutive activation of the mechanistic target of ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…To further confirm these results, Dmp1 Cre mice expressing Cre recombinase under the control of the murine Dmp1 promoter were used as an alternative tool to generate osteocyte specific targeted mutants. [ 21 ] The obtained Dmp1 Cre ;Cd63 fl/+ mice (genotyping identified in Figure S2 B,D, Supporting Information) showed similar eGFP and mCherry expression in the cortex area of brain sections (Figure S3 A,B, Supporting Information). Although Dmp1 Cre mice were widely used in osteocyte‐specific targeting, previous evidence had revealed that it also targeted cells in the mouse cerebellum and hindbrain.…”
Section: Resultsmentioning
confidence: 90%
“…To further confirm these results, Dmp1 Cre mice expressing Cre recombinase under the control of the murine Dmp1 promoter were used as an alternative tool to generate osteocyte specific targeted mutants. [ 21 ] The obtained Dmp1 Cre ;Cd63 fl/+ mice (genotyping identified in Figure S2 B,D, Supporting Information) showed similar eGFP and mCherry expression in the cortex area of brain sections (Figure S3 A,B, Supporting Information). Although Dmp1 Cre mice were widely used in osteocyte‐specific targeting, previous evidence had revealed that it also targeted cells in the mouse cerebellum and hindbrain.…”
Section: Resultsmentioning
confidence: 90%
“…Previous studies have reported that osteocyte regulates myelopoiesis via Gs α -dependent and -independent signaling(Fulzele, et al 2013; Azab, et al 2020). Recent study also reported that osteocyte mTORC1 signaling regulates granulopoiesis via secreted IL-19(Xiao, et al 2021). Meanwhile, sclerostin secreted by osteocyte adversely affects B cell survival(Horowitz and Fretz 2012).…”
Section: Discussionmentioning
confidence: 95%
“…Osteocytes, as the long living terminally differentiated cells and the most abundant cells within the bone matrix(Tresguerres et al 2020), play vital roles in maintaining the skeletal homeostasis. Apart from mechanical transduction(Long 2011; Sato et al 2020), osteocytes have been shown to regulate bone formation, bone resorption, bone marrow hematopoiesis(Asada et al 2013; Azab et al 2020; Fulzele et al 2013; Xiao et al 2021) and generate endocrine signals to mediate function of other organs(Razzaque 2009; Fulzele et al 2017; Cain et al 2012). Here we hypothesize that osteocytes, may exert another important role in regulation of lineage cell fate specifications, and harmonization of bone and bone marrow through mediation of organismal senescence.…”
Section: Introductionmentioning
confidence: 99%
“…It still remains unknown whether IL-19 has additional effects on other organs or tissues but its potential application in neutropenic state is undoubted, being more efficient than granulocyte colony-stimulating factor (G-CSF). Cancer patients who underwent chemotherapy and had reduced activity to promote bone marrow neutrophil formation, had striking downregulation of serum IL-19 ( 24 ).…”
Section: Introductionmentioning
confidence: 99%